Functional Characterization of Wild-type and 49 CYP2D6 Allelic Variants for N-Desmethyltamoxifen 4-Hydroxylation Activity - Muroi, Yuka; Saito, Takahiro; Takahashi, Masamitsu; Sakuyama, Kanako; Niinuma, Yui; Ito, Miyabi; Tsukada, Chiharu; Ohta, Kiminori; Endo, Yasuyuki; Oda, Akifumi; Hirasawa, Noriyasu; Hiratsuka, Masahiro (DRUG METABOLISM AND PHARMACOKINETICS, 2014)
Genetic variations in cytochrome P450 2D6 (CYP2D6) contribute to interindividual variability in the metabolism of clinically used drugs, e.g., tamoxifen. CYP2D6 is genetically polymorphic and is associated with large interindividual variations in therapeutic efficacy and drug toxicity. In this study, we performed an in vitro analysis of 50 allelic variants of CYP2D6 proteins. Wild-type CYP2D6.1 and 49 variants were transiently expressed in COS-7 cells, and the enzymatic activities of the CYP2D6 variants were characterized using N-desmethyltamoxifen as a substrate. The kinetic parameters Km, Vmax, and intrinsic clearance (Vmax/Km) of N-desmethyltamoxifen 4-hydroxylation were determined. Among the 50 CYP2D6 variants, the kinetic parameters for N-desmethyltamoxifen 4-hydroxylation were determined for 20 CYP2D6 variants. On the other hand, the kinetic parameters of 30 CYP2D6 variants could not be determined because the amount of metabolite produced was at or below the detection limit at the lower substrate concentrations. Among them, 8 variants, i.e., CYP2D6.2, .9, .26, .28, .32, .43, .45, and .70, showed decreased intrinsic clearance at <50% of CYP2D6.1. The comprehensive in vitro assessment of CYP2D6 variants provides novel insights into allele-specific activity towards tamoxifen and may be valuable when interpreting in vivo studies.